EVALUATION OF MAXIMAL RESPIRATORY PRESSURES WHEELCHAIR PRE AND POST IN BASKETBALL IN WHEELCHAIR ADAPTED (Fiep Bulletin - online, 2012)
Introduction: Spinal cord injury, regardless of etiology, sets a new routine for the affected, and this requires changes and adaptations in the various roles and activities undertaken so far. It is wheelchair to find new ways to get to experience autonomy and independence in their new activities. The adapted sports emerged after the Second World War in order to handle and socialize the war disabled. The manometer is a simple method is considered useful as a means of evaluating the condition of the respiratory muscle strength in patients with spinal cord injury. Objective: To evaluate respiratory muscle strength before and after the practice of adapted sports basketball on wheels. Methodology: The study will consist of eight male patients suffering from traumatic spinal cord injury complete or incomplete submitted the practice of basketball in a wheelchair, who chose to perform the activity and participate voluntarily in the research, testing the strengthof respiratory muscles through the Commercial unit manuvacuometroMedica. Results: We found values which include pre-program average MIP cm/H2O -99.66 ±23.88. The minimum value found for this pressure was -60cm/H2O and maximum -120cm/H2O. When analyzing the initial maximum expiratory pressure was found to average81.66 ± 22.28 cm/H2O with minimum and maximum 50cm/H2O 110cm/H2O. At the end of the adapted sports program there was average -110 ± 12.64 cm/H2O MIP. The minimum value found for this pressure was -90cm/H2O and maximum -120cm/H2O. When analyzing the end expiratory pressure found an average of 100 ± 16.73 cm/H2O with minimum and maximum 50cm/H2O 110cm/H2O, thus presenting a significant increase in muscle strength. Conclusion:It appears that the sport well suited to promote the interaction pisicosocial wheel chair, increases respiratory muscle strength.
Keywords: muscle strength; Spinal Cord Injury; adapted sports.